Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
45th AIAA Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-3071
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Thick Airfoil Aerodynamics: Experiments, Computation, and Theory

Abstract: An experimental, computational and theoretical investigation was carried out to study the aerodynamic loads acting on a relatively thick NACA 0018 airfoil when subjected to pitching and surging, individually and synchronously. Both pre-stall and post-stall angles of attack were considered. Experiments were carried out in a dedicated unsteady wind tunnel, with large surge amplitudes, and airfoil loads were estimated by means of unsteady surface mounted pressure measurements. Theoretical predictions were based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…However, as far as we know, no experimental research has reported the existence of the sum frequency and difference frequency. A relevant study set the gust fluctuation frequency the same as the model oscillating frequency in experiments for consideration of engineering applications (Strangfeld et al 2015).…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…However, as far as we know, no experimental research has reported the existence of the sum frequency and difference frequency. A relevant study set the gust fluctuation frequency the same as the model oscillating frequency in experiments for consideration of engineering applications (Strangfeld et al 2015).…”
Section: Theoretical Descriptionmentioning
confidence: 99%
“…The CFD solutions are based on unsteady Reynolds-averaged Navier-Stokes (URANS) equations. After conducting thorough verification and validations of multiple URANS solvers with multiple turbulence closure models, Rumsey showed that URANS-based models have a very limited ability to model cases with separation (Stangfeld et al, 2015;Rumsey, 2016). Furthermore, the tendency of URANS codes to smear vorticity will cause errors in the wake induction for cases in which the blades are modelled.…”
Section: Comparison Casesmentioning
confidence: 99%
“…Numerical simulations have also been used as an effective way to further understand these effects. Numerical investigations on a quasi-3D model include that of Visbal [3] and Gross and Wen [4], with a high-order finite difference based large eddy simulation (LES), and Strangfeld [5], with unsteady Reynolds-averaged Navier-Stokes (URANS) simulations. Hodara et al [6] investigated a pitching airfoil in a constant reverse flow (leading to a reserve dynamic stall) through a joint wind tunnel testing and numerical simulation based on a hybrid RANS-LES approach.…”
Section: Introductionmentioning
confidence: 99%